Genomic Insights into Fusarium verticillioides Diversity: The Genome of Two Clinical Isolates and Their Demethylase Inhibitor Fungicides Susceptibility - Luca Degradi; Valeria Tava; Maria Carmela Esposto; Anna Prigitano; Daniela Bulgari; Andrea Kunova; Marco Saracchi; Paolo Cortesi; Matias Pasquali (Pathogens, 2024)
Fusarium verticillioides is an important plant pathogen in maize and other cereals that is seldom detected as the cause of human fusariosis. Here, we provide the analysis of the available diversity of F. verticillioides sequenced worldwide and report the first two genome assemblies and annotations (including mitochondrial DNA) of Fusarium verticillioides from clinical settings. Fusarium verticillioides 05-0160 (IUM05-0160) and Fusarium verticillioides 09-1037 (IUM09-1037) strains were obtained from the bone marrow and blood of two immunocompromised patients, respectively. The phylogenomic analysis confirmed the species identity of our two strains. Comparative genomic analyses among the reannotated F. verticillioides genomes (n = 46) did not lead to the identification of unique genes specific to the clinical samples. Two subgroups in the F. verticillioides clade were also identified and confirmed by a mitochondrial diversity study. Clinical strains (n = 4) were positioned in the multigene phylogenetic tree without any correlation between the host and the tree branches, grouping with plant-derived strains. To investigate the existence of a potential fitness advantage of our two clinical strains, we compared demethylase inhibitor fungicides susceptibility against the reference Fusarium verticillioides 7600, showing, on average, lower susceptibility to agricultural and medical-used antifungals. A significant reduction in susceptibility was observed for itraconazole and tetraconazole, which might be explained by structural changes in CYP51A and CYP51C sequences. By providing the first two annotated genomes of F. verticillioides from clinical settings comprehensive of their mitogenomes, this study can serve as a base for exploring the fitness and adaptation capacities of Fusarium verticillioides infecting different kingdoms.